2014
DOI: 10.15252/embj.201387500
|View full text |Cite
|
Sign up to set email alerts
|

Neutral competition of stem cells is skewed by proliferative changes downstream of Hh and Hpo

Abstract: Neutral competition, an emerging feature of stem cell homeostasis, posits that individual stem cells can be lost and replaced by their neighbors stochastically, resulting in chance dominance of a clone at the niche. A single stem cell with an oncogenic mutation could bias this process and clonally spread the mutation throughout the stem cell pool. The Drosophila testis provides an ideal system for testing this model. The niche supports two stem cell populations that compete for niche occupancy. Here, we show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
127
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(138 citation statements)
references
References 80 publications
(143 reference statements)
11
127
0
Order By: Relevance
“…Thus, Ci not only functions as transcription factor to activate Hh-responsive target genes, but also inhibits Hpo-Wts kinase cascade activity, thus enhancing Yki signaling in certain biological contexts. The Hh and Hippo signaling pathways have been recently shown to control common biological events; however, the molecular mechanisms underlying the crosstalk between these two pathways are largely unknown [49,50]. It was reported that the Hh signaling transcriptionally activated yki in follicle stem cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Ci not only functions as transcription factor to activate Hh-responsive target genes, but also inhibits Hpo-Wts kinase cascade activity, thus enhancing Yki signaling in certain biological contexts. The Hh and Hippo signaling pathways have been recently shown to control common biological events; however, the molecular mechanisms underlying the crosstalk between these two pathways are largely unknown [49,50]. It was reported that the Hh signaling transcriptionally activated yki in follicle stem cells [50].…”
Section: Discussionmentioning
confidence: 99%
“…The JAK-STAT pathway, the EGFR pathway, the Hpo pathway and the Hh pathway are the major players currently identified in regulating CySCs (Amoyel et al, 2014;Kiger et al, 2000Kiger et al, , 2001Michel et al, 2012;Tran et al, 2000;Tulina and Matunis, 2001). Are the phenotypes induced by SUMO pathway suppression mediated by one of them?…”
Section: The Sumo Pathway Genetically Interacts With the Hh Pathwaymentioning
confidence: 99%
“…1A). Several signaling pathways have been reported to regulate CySCs, including the JAK-STAT pathway (Issigonis et al, 2009;Kiger et al, 2001;Leatherman and DiNardo, 2010;Singh et al, 2010;Tulina and Matunis, 2001), the EGFR pathway (Eun et al, 2014;Kiger et al, 2000;Tran et al, 2000), the Hpo pathway (Amoyel et al, 2014) and the Hh pathway (Amoyel et al, 2013;Michel et al, 2012;Zhang et al, 2013b). Although these pathways govern stem cell behavior, the function of PTMs during this process is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…The other daughter cell is displaced from the niche and begins to differentiate (de Cuevas and Matunis, 2011). Although CySCs do not divide asymmetrically, their divisions generate a daughter cell that is maintained as a CySC and a daughter cell that begins to differentiate (Cheng et al, 2011;Amoyel et al, 2014). As the displaced germ cell exits the niche, it is encapsulated by two CySCs that remain wrapped around the differentiating gemline cyst until the end of spermatogenesis .…”
Section: Introductionmentioning
confidence: 99%